THE EFFECT OF MANAGEMENT ACCOUNTING SYSTEMS ON FIRM PERFORMANCE : STUDIES IN VARIOUS COUNTRIES - Fauziyyah, Nurul (MIZANIA: Jurnal Ekonomi Dan Akuntansi, 2021)
Abstract Uncertainty will always be present and be a challenge for companies or organizations if they want to continue to exist and develop. The rapid changing era and technological developments require companies or business to improve the performance of companies or organizations in the midst of increasing competitive pressure. This makes Management Accounting System (MAS) as a very fundamental tool for companies or organizations to support management in the decision-making process. The changes that occur can affect the characteristics of MAS in each company or organization and also the differences in the needs and conditions of the company are the causes of these differences. This study aims to provide an overview of what and how the influence of the Management Accounting System (MAS) on the performance of companies in various countries. This study is a literacy study based on theoretical descriptions, findings and other research materials obtained from reference materials. The data analysis method in this research is descriptive analysis method by going through the stages of collecting data from various national and international journals, reviewing data, analyzing data, and drawing conclusions. The findings of this study indicate that there are previous studies that are in line with the argument that states the influence of MAS on company performance, but there are also previous studies that are not in line with this argument. These differences exist because the implementation and design of MAS in various companies and organizations is associated with contingency factors such as technology, organizational structure, environment, and many more. Keywords: Management Accounting System (MAS), Firm Performance, Organizational Performance